Effect of early enteral nutrition on intestinal permeability, protein-losing enteropathy and outcome in canine parvoviral enteritis - Jacobson, Linda S. (University of Pretoria, 2013)
Dissertation (MMedVet (Med))--University of Pretoria, 2002.